Decoy Exosomes Offer Protection Against Chemotherapy‐Induced Toxicity. Issue 32 (4th September 2022) - Fan, Miao; Li, Hang; Shen, Deliang; Wang, Zhaoshuo; Liu, Huifang; Zhu, Dashuai; Wang, Zhenzhen; Li, Lanya; Popowski, Kristen D.; Ou, Caiwen; Zhang, Kaihan; Zhang, Jinchao; et al.
Abstract: Cancer patients often face severe organ toxicity caused by chemotherapy. Among these, chemotherapy‐induced hepatotoxicity and cardiotoxicity are the main causes of death of cancer patients. Chemotherapy‐induced cardiotoxicity even creates a new discipline termed "cardio‐oncology". Therefore, relieving toxicities induced by chemotherapy has become a key issue for improving the survival and quality of life in cancer patients. In this work, mesenchymal stem cell exosomes with the "G‐C" abundant tetrahedral DNA nanostructure (TDN) are modified to form a decoy exosome (Exo‐TDN). Exo‐TDN reduces DOX‐induced hepatotoxicity as the "G‐C" base pairs scavenge DOX. Furthermore, Exo‐TDN with cardiomyopathic peptide (Exo‐TDN‐PCM) is engineered for specific targeting to cardiomyocytes. Injection of Exo‐TDN‐PCM significantly reduces DOX‐induced cardiotoxicity. Interestingly, Exo‐TDN‐PCM can also promote macrophage polarization into the M2 type for tissue repair. In addition, those decoy exosomes do not affect the anticancer effects of DOX. This decoy exosome strategy serves as a promising therapy to reduce chemo‐induced toxicity. Abstract : Chemotherapy is effective but can induce severe liver damage and cardiotoxicity. A new discipline called "cardio‐oncology" is developed rapidly to address those concerns. In this work, exosomes are used as a carrier for tetrahedral DNA nanostructure (TDN) to form a decoy exosome (Exo‐TDN) that can absorb excess DOX and mitigate cardiac and liver toxicity caused by DOX therapy.